Penggunaan Metode Single Exponential Smoothing dalam Peramalan Produksi Buah Nanas - Simon, Gusman (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
Forecasting is an activity that uses past data to predict future conditions. By using historical data on pineapple production levels, forecasting is necessary as a projection analysis that supports the concept of commodity development and the design of planting, production, and distribution management programs. Based on data patterns over the past 12 years, forecasting is carried out using the single exponential smoothing method. The purpose of this study is to forecast the level of pineapple production in Lampung Province in 2025. The data used is the pineapple production level from 2013 to 2024, obtained from the Lampung Province BPS virtual website. Alpha, as a smoothing coefficient in the forecast, is selected using the Solver facility in MS. Excel to obtain the lowest MAPE value. Searching for alpha values ​​in the range of 0 to 1 produces a value of 0.941434907646866. The forecasting results show that the production level in 2025 is 6991081.608 quintals, with a MAPE value of 13.099%, which indicates a good level of forecasting accuracy.